Toward the African Revolution: Political Essays - Fanon, Frantz, 1925-1961.; Chevalier, Haakon (New York : Grove Press, 1988)
This powerful collection of articles, essays, and letters spans the period between Black Skin, White Masks (1952) and The Wretched of the Earth (1961), Fanon$1 (Bs landmark manifesto on the psychology of the colonized and the means of empowerment necessary for their liberation. These pieces display the genesis of some of Fanon$1 (Bs greatest ideas that became so vital to the leaders of the American civil rights movement.s
Includes bibliographical references.
Keywords: French--Algeria--History.; Algeria--History--Revolution, 1954-1962.